DINAMIKA INTERAKSI SOSIAL PADA PAGUYUBAN PASUNDAN DI KOTA TERNATE - Nurjaman, Enang Yusuf (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi; Vol 15 No 1 (2019), 2020)
Sundanese as the second largest ethnic group after Java, known as a tribe who does not like to migrate, comfortable natural conditions and the stigma of "kurung batokeun" may be one of the reasons why Sundanese do not like to wander. However, as the development, many Sundanese tribes who do unity, not only wander within the country but wander throughout the world, so that the Sundanese known not to wander began to break. One of the destinations to wander the Sundanese tribe is Ternate City of North Maluku. The research  purposse to determine social interaction and communication patterns among fellow immigrants from the Sundanese who are members of the Paguyuban Pasundan, because they want to see a culture of communication in depth, this study uses qualitative ethnographic communication research. The conclusions resulting from this research (1) Social interaction between Sundanese tribes in the Paguyuban Pasundan is conducted intensively, a feeling of equality and interaction is carried out very well. (2) The pattern of communication among Sundanese tribes who are members of the Paguyuban Pasundan, is easy to open, without obstacles, is equivalent to quality and very significant good communication